Analysis of the life cycle applied in the fishmeal and fish oil industry in fishing plants in Huacho, Carquín and Vegueta, Huaral, Lima, 2018-2019 - Cabrera Carranza, Carlos Francisco (2020)
The fish oil and flour industry is one of the main productive activities in the country, however, the volumes of organic waste discharged into the marine environment are high. Life Cycle Analysis (LCA) is applied with an emphasis on liquid residues in fishing plants in Huacho, Carquín and Vegueta in Huaura. Lime. The research is applied, descriptive and comparative, it develops a qualitative - quantitative approach. According to ISO 14001, the significant environmental aspects identified include the reception and storage of raw materials, cooking, draining, pressing, separation, centrifugation, grinding, drying, dosing of antioxidant, bagging, energy generation, evaporation of cola water, broth treatment, industrial effluent treatment, machinery maintenance. In the matter and energy balance for a plant of 84 MT / hour, the production yield is fish / flour: 4,150 and for Fish / Oil: 6,307. The main impact is associated with the volumes of waste water discharged containing organic load, which increase the concentration of suspended solids, fats and oils and biochemical oxygen demand, which exceed the maximum permissible limit (LMP).